Regenerating Bodies. (January 2018) - Fisch, Michael
This article is an expanded commentary on the essay "The Social Life of 'Scaffolds': Examining Human Rights in Regenerative Medicine." In discussing the limits and possibilities of the essay, this commentary suggests that problematizing scaffolds in regenerative medicine as a kind of infrastructure rather than prosthetic opens the way for an understanding of the genesis of regenerative assemblages in ways that help to reframe inherent issues of human rights. Ultimately, it proposes the notion of experimental ecologies as a way of thinking about an ethically driven productive entanglement of bodies, environments, and technology.